Effects of Chlamydia trachomatis infection on sperm chromatin condensation and DNA integrity. (6th November 2017) - Dehghan Marvast, L.; Talebi, A. R.; Ghasemzadeh, J.; Hosseini, A.; Pacey, A. A.
Summary: The present study was performed to investigate the relation of Chlamydia trachomatis infection to sperm chromatin/DNA integrity in a population of infertile men (male partner of infertile couples) from Iran. Blood, semen and first‐void urine samples were obtained from 250 infertile men. Data were analysed with regard to the results of (i) serological analysis for specific antibodies to C. trachomatis in serum; (ii) the presence of C. trachomatis and DNA in first‐void urine; and (iii) in the semen sample of the male partner, in addition to sperm analysis, four different tests (aniline blue, chromomycin A3, acridine orange and TUNEL) were used to detect sperm chromatin and DNA abnormalities. The main conclusions of the results were: (i) no evidence of C. trachomatis infection in semen samples was found; (ii) sperm DNA fragmentation and chromatin studies were not correlated with C. trachomatis diagnosis; (iii) the percentage of DNA fragmentation is positively correlated with the percentage of immotile sperm but negatively with semen volume, normal morphology; and (iv) in sperm chromatin evaluations, only the percentage of chromatin protamination was related to male age.